LITERASI DIGITAL SEBAGAI PROSES PEMBERDAYAAN PELAKU UMKM DALAM MENINGKATKAN KEBERLANJUTAN USAHA DI KOTA SURABAYA - Dhelittya Finaliyani Putri (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2026)
This study aims to explore how digital literacy functions as an empowerment process for Micro, Small, and Medium Enterprises (MSMEs) in enhancing business sustainability in the digital era. The rapid growth of digital transformation requires MSME actors not only to possess technical skills but also to interpret, manage, and strategically utilize digital information in their business activities. This research employs a qualitative approach using a phenomenological method to capture the experiences, meanings, and practices of digital literacy among MSME actors. Data were collected through in-depth interviews, observations, and documentation with purposively selected informants. The findings reveal that digital literacy extends beyond technical competence, serving as an empowerment process that enhances individual capacity, self-confidence, creativity, and the ability to build relationships with customers. Furthermore, digital literacy enables MSME actors to be more adaptive to market changes, expand business networks, and develop innovative marketing communication strategies. The study also highlights that social, cultural, and resource access factors influence the level of digital literacy and business sustainability. Therefore, digital literacy emerges as a crucial element in strengthening the resilience and sustainability of MSMEs within the dynamic digital economy. Keywords: Digital Literacy, Empowerment MSMEs, Business Sustainability, Marketing Communication